Japanese Occupation Government Policy in Indonesia On Culture and Literature: a case study of asia raja newspaper (1942-1945) - Maman S. Mahayana (UPP FIB UGM (No.02;Juni 2013;Vol.25), 2013)
Japanese Occupation Government Policy in Indonesia On Culture and Literature: a case study of asia raja newspaper (1942-1945) : budaya, kebijakan pemerintah, pendudukan jepang, politik kolonial, sastra,surat kabar asia raja